2021
DOI: 10.1021/acs.orglett.1c03517
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Sequential Vinyl C–H Activation/Dual Decarboxylation: Regioselective Synthesis of Phenanthrenes and Cyclohepta[1,2,3-de]naphthalenes

Abstract: The application of a C(vinyl), C(aryl)-palladacycle from vinyl-containing substrates is challenging due to the interference of a reactive double bond in palladium catalysis. This Letter describes a [4 + 2] or [4 + 3] cyclization based on a C(vinyl), C(aryl)-palladacycle by employing α-oxocarboxylic acids as the insertion units under a palladium/air system. The reaction proceeded through the key vinyl C−H activation and dual decarboxylation sequence, forming phenanthrenes and cyclohepta[1,2,3de]naphthalenes reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…On the basis of the above experimental results and previous work, 10–14,18 we propose a plausible mechanism for this protocol (Scheme 3). First, arylpalladium( ii ) species A is generated by oxidative addition of the C–Br bond in 1a to Pd(0), which is subsequently converted into intermediate B via an intramolecular aminopalladation by the coordination of Pd( ii ) to alkyne.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…On the basis of the above experimental results and previous work, 10–14,18 we propose a plausible mechanism for this protocol (Scheme 3). First, arylpalladium( ii ) species A is generated by oxidative addition of the C–Br bond in 1a to Pd(0), which is subsequently converted into intermediate B via an intramolecular aminopalladation by the coordination of Pd( ii ) to alkyne.…”
Section: Resultssupporting
confidence: 61%
“…1 In the past few decades, five-membered C , C -palladacycle-based reactions have attracted widespread attention due to their versatile conversions in which two C–Pd bonds could be functionalized by trapping with coupling reagents. 2–16 Among them, of extraordinary interest to synthetic chemists are cyclizations of five-membered C , C -palladacycles with various coupling reagents such as aryl halides, 3 arynes, 4 alkynes, 5 diaziridinones, 6 diazo compounds, 7 bromophenols, 8 dibromomethane, 9 halogenated carboxylic acids, 10–14 etc ., which have emerged as a powerful tool for the construction of polycyclic compounds. Recently, the groups of Kwong, us and others achieved the transformation of five-membered C , C -palladacycles by various halogenated carboxylic acids via a carboxyl-assisted palladacycle capture strategy, leading to the construction of diverse fused polycycles (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, our group and others designed various halogenated carboxylic acids as C1, C2 or C3 insertion units to construct different size-ring fused cyclic compounds via this strategy. [53][54][55][56][57][58][59][60][61][62] In these reactions, it was observed that the inser- tion of carboxylic acids usually showed good regioselectivity. Thus, the methods used o-halobenzoic acids, arynes and aryl halides as aromatic ring precursors, which could be complementary.…”
Section: Palladium-catalysed Intermolecular C-h Annulation Of Aryl Ha...mentioning
confidence: 99%
“…Using BQ as a oxidant, Wu 54 developed a method for synthesizing phenanthrenes and cyclohepta[1,2,3-de]naphthalene using 2-iodophenylethylene and α-oxocarboxylic acids (Scheme 38). This method overcame the interference of a reactive double bond to form a C(aryl),C(aryl)-palladacycle through Organic & Biomolecular Chemistry Review vinyl C-H activation, and had special regioselectivity for nonsymmetrical PAHs.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%